Euler-Rodrigues Rotation for computes the tangent vector and curvature vector of the intersection curve of two surface in 3D Lorentz-Minkowski space - Aléssio, Osmar (2025)
We present method computes the tangent and curvature vector of the intersection curve of two surface, parametric/implicit or implicit/implicit, in Lorentz-Minkowski space E3, by applying a Euler-Rodrigues rotation to a vector projected onto the tangent space. The axis of rotation is the normal vector of the surface (the surfaces can be timelike, spacelike or lightlike), therefore three types of rotations, since the normal vectors can be: spacelike, lightlike, or timelike.